Povezanost između povišenog statusa gvožđa i rizika od preeklampsije: sistematski pregled i meta-analiza: Hepcidin associated with Preeclampsia - Li, Changhong; Xu, Xiaohui; Qian, Min (Journal of Medical Biochemistry, 2026)
Background: This review aims to conduct a comprehensive and systematic report of the currently published information on the association between elevated hepcidin levels and the risk of preeclampsia by meta-analysis of published prospective case-control studies or cross-sectional studies combined with follow-up to provide a comprehensive and reliable basis for early intervention and clinical decision making in the disease. Methods: We searched five databases such as Pubmed, Web of Science, Cochrane, China National Knowledge Infrastructure, and WAN FANG DATA to retrieve articles related to the relationship between elevated levels of hepcidin and the risk of preeclampsia up to February 2025. We calculated the standardized mean deviation (SMD) and 95% confidence interval (95% CI) for comparison using a random-effects model. Results: A total of 8 articles were included in this review. The results found that higher serum hepcidin and serum iron levels and lower serum transferrin levels were observed in pregnant women presenting with preeclampsia compared with normotensive pregnant women (serum hepcidin: SMD = 1.08, 95%CI: 0.03, 2.14; serum iron: SMD = 0.63, 95%CI: 0.41, 0.86; serum transferrin: SMD = -0.50, 95%CI: -0.73, -0.27). Conclusions: Similar to the previous review, this systematic review and meta-analysis showed that high serum iron levels might be associated with a higher risk for preeclampsia. In addition, this meta-analysis summarized two mechanisms for the failure of hepcidins to reduce serum iron levels in pregnant mothers with preeclampsia in late pregnancy. And this meta-analysis would guide further clinical studies.